Political Education for Palangka Raya Youth to Promote Integrity in the 2024 Regional Elections - M. Doddy Syahirul Alam; Iskandar, Dian; Satriawan, Bismar Harris; Ummu Habibah Gaffar (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The issue of money politics poses a serious threat to the integrity of democracy at both national and local levels. It opens the door for political figures without integrity, while voter preferences are driven more by pragmatism than rationality. This issue demands special attention to ensure that the electoral democratic process is not controlled by capital. Therefore, political education is needed for voters, especially the youth of Palangka Raya, to promote integrity in the 2024 local elections through community service activities. This initiative targets young voters in Palangka Raya, particularly those registered for the 2024 Regional Head Election. The activity is carried out through an educational approach related to voter integrity values and resistance to money politics, culminating in a survey of voters' understanding of the materials presented. This activity was conducted in collaboration with the Election Supervisory Board (Bawaslu) of Central Kalimantan. The results show that participants have a better understanding of voter integrity and the negative impact of money politics. Furthermore, this initiative is expected to raise awareness of the importance of political participation and encourage young voters to reject money politics in future elections.